ANALYSIS ON THE ECONOMIC POTENTIAL AND COMPETITIVE ADVANTAGES OF SOUTH TANGERANG CITY IN BANTEN PROVINCE IN THE PERIOD OF 2012 – 2016 - Januar Irfan Gaffar (Jurnal Ilmiah Mahasiswa FEB, 2017)
In this era of globalization, economic development has an important role and can also be called as one effort to create community welfare. Therefore, the results of development should be enjoyed by all people as a form of welfare improvement in a fair and equitable. This research has a purpose to know the leading economic sectors in South Tangerang City, Banten Province in order to increase economic growth of South Tangerang City. The analysis is done by comparing GRDP on the basis of Constant Price of Malang City 2010 and GRDP series based on Constant Price of Banten Province 2010. The analysis model used is Location Quotient (LQ) analysis, Shift Share analysis, Growth Ratio Model (MRP) and Klassen Typology analysis,Based on the results of research, tertiary needs become an important role in economic growth, but the development planning of South Tangerang City can be directed to the leading sectors can encourage the acceleration of regional development in accordance with the identification of potentials through analysis tools in this research so that the policy formulation of South Tangerang City able to accurately regarding resources and potential owned by South Tangerang City in order to increase economic growth.According to the results of analysis tools typology klassen South Tangerang City has a superior economic sector and grow rapidly compared with the same sector in the province of Banten only (a) Large and Retail Trade: Car Repair and Motorcycles. Keywords: economic development, economic sectors seed, location quotient, shift share, the ratio of growth model, typology klassen.